EKSISTENSI SENI PERTUNJUKAN TARI REJANG SARI DI DESA SUMERTA KECAMATAN DENPASAR TIMUR - Ni Made Ayik Bulan Agustina Maha Dewi; I Gede Gusman Adhi Gunawan (WIDYANATYA, 2021)
Rejang Sari was created by I Ketut Rena in 2017 and is still being preserved by the community. The Rejang Sari dance was first performed at the odalan in Banjar Pande and was first published during the Calonarang performance at the Sumerta Village Temple. With the publication of media, the existence of this dance can be known by the public, especially in Sumerta Village. The research used is qualitative research, using data collection methods based on the results of observations, interviews, and literature studies. The data sources used are primary and secondary data sources. Furthermore, data analysis methods are used which include data reduction, data presentation, and drawing conclusions.The result of the research is the existence of the performing arts of Rejang Sari Dance until now its existence is still maintained by the supporting community. Judging from several religious ritual activities in Sumerta Village, this dance is still performed, which functions at the time of ngider bhuana and memendak. Likewise, when there are ritual activities in several banjars in Sumerta Village, they perform the Rejang Sari Dance using full make-up and clothing, some only use traditional prayer clothes. The factors that make this dance still survive, namely the existence of internal factors and external factors, so that without realizing it through this Rejang Sari performance and accompanied by media publications can make Rejang Sari Dance still exist today.